Role Playing Game (RPG ) Video Games and Loneliness: An Analysis of Finding Paradise Narrative - Saraswati, Listya Ayu; Rifai, Irfan; Farhan, Muhamad (Lingua Cultura, 2022)
The research argued that ‘Finding Paradise’, the third installment of adventure RPG video games developed and published by Freebird Games, embodied excellent storytelling techniques for illustrating loneliness and those who experienced it in society. The ‘Finding Paradise’ narrative used immersive technology to let players experience the subject at hand with their own senses. Video game design aimed for relevancy to contemporary society’s realities as well as compelling storytelling. Close reading was used to break down ‘Finding Paradise’ narratives into smaller aspects to strengthen and articulate a more connected relationship with the text; as a result, the researchers could draw interpretations within the text. By incorporating Herman’s fundamental narrative components into the ‘Finding Paradise’ narrative and examining how stories and narratives can be used as a teaching tool using the reader-response approach, it can be concluded that the subcomponents of the game’s narrative, specifically the representation of situatedness, event sequencing, worldmaking, and reality representation, provide a good example of developing a well-crafted and non-judgmental representation of loneliness as a mental illness and individuals who suffer from it that can also be used in EFL/ESL classroom.